2014
DOI: 10.1159/000367810
|View full text |Cite
|
Sign up to set email alerts
|

Single-Lesion Measurement per Organ for Assessing Tumor Response in Advanced Gastric Cancer

Abstract: Objective: The criterion of two target lesions per organ in the revised Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1) is an arbitrary decision. We assumed that measuring the single largest lesion per organ (modified RECIST 1.1, hereafter referred to as mRECIST 1.1) instead of two (RECIST 1.1) might be enough to assess tumor responses. Methods: We compared tumor response using computed tomography according to the RECIST 1.1 and mRECIST 1.1 in patients with advanced gastric cancer (AGC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…The study was designed this way because the purpose was to validate the observations in the prior studies that followed the same strategy and demonstrated a significant association between volume and survival. The prior studies by others also demonstrated that the single-lesion approach provides concordant response assessment with multiple-lesion assessment in lung and other cancers 43-45 . We believe that tumor volume should be used as an additive method to the conventional measures such as RECIST, which is designed to capture the systemic tumor burden with a simple and practical method 15, 21, 46 .…”
Section: Discussionmentioning
confidence: 89%
“…The study was designed this way because the purpose was to validate the observations in the prior studies that followed the same strategy and demonstrated a significant association between volume and survival. The prior studies by others also demonstrated that the single-lesion approach provides concordant response assessment with multiple-lesion assessment in lung and other cancers 43-45 . We believe that tumor volume should be used as an additive method to the conventional measures such as RECIST, which is designed to capture the systemic tumor burden with a simple and practical method 15, 21, 46 .…”
Section: Discussionmentioning
confidence: 89%
“…Patients' baseline characteristics are summarized in Table 1 according to the primary site. There were a total of 153 patients who met the inclusion criteria: 64 with NSCLC 13 , 51 with GC 14 , and 38 with CRC 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Among 51 patients with metastatic GC 14 , twenty-five patients (49.0%) had poorly differentiated adenocarcinoma. The most common metastatic site with target lesions was the liver (58.8%), followed by the LNs (54.9%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations